Regression of large periapical lesion using calcium hydroxide therapy: a six-year follow-up case report - Cari Maristela Pieper; Eliseu Aldrighi Münchow; Evandro Piva (Brazilian Dental Science)
Periradicular lesions occur in non-vital teeth as the result of a chronic aggression by the presence of microorganisms into the root canal, which may appear as a radiolucent lesion in the radiographic exam; treatment varies according to surgical or nonsurgical methods. This case report describes the regression of a periradicular lesion using a nonsurgical endodontic treatment in association with intracanal calcium hydroxide-based medicament. After patient examination and radiographic analysis, a 13 mm (in maximum diameter) radiolucent lesion was observed in tooth number 12. The endodontic treatment was done and Calen-CMCP (S.S. White Artigos Dentários Ltda., Rio de Janeiro, RJ, Brazil) was placed into the root canal, which was changed after every two weeks during two months. It was observed a progressive centrifugal regression of the lesion after every renewing of the medicament. In addition, after six-year follow-up the tooth was still free of re-infection and bone tissue was completely regenerated. In conclusion, calcium hydroxide therapy can conservatively stimulate the regression of large periradicular lesions.